Analysis of Physical Properties for Various Compositions of Reusable LMG and LCV Micelle Gel - Kang, Jin Mook; Lee, Dong Han; Cho, Yu Ra; Hwang, Seon Bung; Ji, Young Hoon; Ahn, So Hyun; Keum, Ki Chang; Lee, Re Na; Cho, Sam Ju; Noh, Insup (Progress in Medical Physics, 2016)
In this study, we evaluated the reusable leuco malachite green (LMG) micelle gel properties dependent on various components of chemical concentration and compared with leuco crystal violet (LCV). The gels were delivered to 10, 20, 30, 40 and 50 Gy at 6 MV photon beam from linear accelerator and analyzed using spectrophotometry. We confirmed that the reusable LMG and LVC absorbance wavelength peak were made up at 630 nm and 600 nm respectively. The transparency of reusable LMG decreased with higher amount of trichloroacetic acid (TCAA) and lower reusable LMG dyes. 1 mM reusable LMG was the lowest transparency. The sensitivity was increased depending on lower trichloroacetic acid (TCAA) concentrations and the amount of suitable surfactant (Triton X-100), which was found to be 7 mM. However, we were not able to investigate sensitivity effects factor from reusable LMG dyes. The gel dosimeter containing 16 mM TCAA, 7 mM Triton X-100 gel dosimeter showed the highest sensitivity at 0.0021±0.0001 cm−1. Gy−1. The sensitivity of LCV was found to be higher than reusable LMG at 0.0037±0.0005 cm−1. Gy−1. The reusable LMG and LCV dose responses were shown to be R2=0.997, R2=0.999 respectively, as stable measurement results. Future research is necessary to improve dose sensitivity, dose rate dependency and gel fading with extensive chemical formulations. KCI Citation Count: 0